(untitled) (Research, Society and Development, 2022)
Context: Motherhood presents itself as an event which different meanings can be attributed according to the moment and who is involved with this experience. Historically, the required forms of care that relapse on women follow a pattern of norms that vary according to the culture which they are inserted. In the Brazilian context, a series of expectations about what is a good mother, at what age to have children and other surveillance norms. However, for women with disabilities there are other “marks”, like the prejudice. Objective: Present the steps that will be followed and describe the path taken to prepare a scope review, whose emphasis will be on mapping the knowledge about the reality of women wiht disabilities who experience motherhood and to what extent reproductive rights are considered. Method: A scope review will be conducted as recommended at the Joanna Briggs Institute (JBI). We will follow the following steps in the research: formulation of the question; identification of relevant studies; selection of studies; data extraction; separation, summarization and reporting of results. Results: Results will be published. Conclusion: We hope to map knowledge and identify gaps in order to guide further research in the area.